Travail, Mémoires et Femmes dans la ceinture industrielle de Lisbonne (Portugal) - Inês Fonseca (Conserveries Mémorielles)
Among the women from Baixa da Banheira (a parish in the industrial belt of Lisbon) one mystery persists: which plants use to employ the feminine work force?The whole industrial belt underwent a swift process of industrialization however the stability that this offered to this working class population was short lived. While Baixa da Banheira was a pole of attraction, during the sixties, the region experienced a slow decline in the eighties. Over the last 3 decades this deindustrialization has accelerated to the point where industry has been replaced by the tertiary sector of activity. Change in the economic activity in the region has meant that a large percentage of these workers have been made redundant. Those still employed have seen their employment conditions and the social rights associated with work erode.For the most part, women continue to be limited to unpaid domestic work (as housewives) or poorly paid informal jobs (which are done at home, as babysitters, cleaners, dressmakers, cooks, etc.). Consequently, they have always been the first to constitute social networks of support as well as the first to resort to those networks – through the informal groups of relatives, neighbours, friends co-workers and also through more formal groups, like local associations and cooperatives of production.